Collected papers from the National Cancer Center Research Institute. - Kokuritsu Gan Senta. Kenkyusho (Tokyo, National Cancer Center., 1962)
Consists of articles reprinted from various journals.
Summaries in English.
Keywords: Neoplasms -- Periodicals; Research -- Periodicals